ANALISIS PENGARUH JUMLAH CLIENT DAN JARAK CAKUPAN WIRELESS AP IEEE 802.11 N TERHADAP KUALITAS JARINGAN WLAN MENGGUNAKAN TEKNIK UR DAN WDS - Ilmiatul Hafazah; I Wayan Agus Arimbawa; Andy Hidayat Jatmika (Informatics Engineering Dept., Faculty of Engineering, University of Mataram, 2018)
The most widely circulated standard WLAN network in the market today is IEEE 802.11n. To build a more practical WLAN network using UR and WDS techniques. This study aims to measure and analyze the effect of the number of clients and distance to the quality of WLAN networks using UR and WDS techniques with parameters of bandwidth, jitter, and packet loss. The results of data analysis are known that the more clients and the further distance the transmission can reduce the quality of UR and WDS networks. The best network quality is generated UR network at 7.5 m distance with bandwidth average of 11934.7035 Kbps, jitter average 2,3563135 ms, and packet loss average 1.90% compared to WDS network with average bandwidth 3846.9135 Kbps, average jitter 9.496095 ms, and packet loss average 5.23%. The worst quality network produced by WDS network at 30 m distance with bandwidth average of 898.32735 Kbps, jitter average of 37.32591 ms, and the average packet loss of 47.10% compared to UR network with an average bandwidth of 8859,797 Kbps, the average jitter 13.082195 ms, and the average packet loss of 19.24%. The overall result of the measurement is known that UR technique is superior to WDS in building a WLAN network.